The Effectiveness of the Discovery Learning Model Supported by the Assemblr Edu Platform on Student Activeness - Nayla Prima Eddelweis; Susilawati Susilawati; Dewi Yulianawati (Journal of Educational Sciences, 2026)
This study was motivated by the low level of Learning Activeness among fifth-grade students at SDN Kahiyangan regarding the human respiratory system due to the limited use of learning hmodels and instructional media. This study aims to examine the effect of the Discovery Learning model supported by the Assemblr Edu platform on students Learning Activeness. The novelty of this study lies in the integration of the Discovery Learning model with Assemblr Edu media to enhance students’ learning activeness in the human respiratory system topic; previous studies generally examined these two variables separately. This study employed a quantitative method using a pre-experimental model and a one-group pretest-posttest design involving 20 students, with purposive sampling used as the sampling technique. The data analysis used was the Wilcoxon signed-rank test. The results showed a significance value of 0.000 (0.000 < 0.05), while the N-Gain score was 0.3429, indicating moderate effectiveness. The use of the Assemblr Edu platform to support the Discovery Learning model helps visualize abstract concepts related to the human respiratory system through three-dimensional objects. Based on the research results, it can be concluded that the Discovery Learning model supported by the Assemblr Edu platform is effective in improving students Learning Activeness.